Diseño de equipamiento turístico basado en las experiencias naturales del contexto de la totora en la laguna de Colta - Espinoza Vaca, Alison Nicole (2023)
The interpretation of data obtained from the investigation of the community surrounding the Colta Lake, which was conducted within the research project "Social design as a potentiator of sustainable tourism in the Colta Lake" shows the low level of management to generate strategic alliances by responsible leaders of the Colta canton and thanks to studies by the Ministry of Tourism, there is little interest in the area of the Colta Lake and the church of Balbanera by domestic and foreign tourists, To this is added the lack of waste of native materials such as totora reeds to develop projects, due to the lack of knowledge of the properties of the fiber as a material by local artisans. Therefore, the objective of this project is to develop a design proposal for tourist equipment based on the language and experiences provided by the natural environment of the totora reed in the Colta Lake through the conceptualization of the space. For which we used the Design Thinking as a methodology, which was chosen to empathize with our main actors (tourists, artisans, and regulators of the sector) and to contribute with a design that responds to the real needs of the context and at the same time respects the natural environment.